1996
DOI: 10.1074/jbc.271.21.12542
|View full text |Cite
|
Sign up to set email alerts
|

ADP-ribosylation of the G Protein Rho Inhibits Integrin Regulation of Tumor Cell Growth

Abstract: Using a gastric derived tumor line, we investigated the involvement of ␤1 integrin and Rho in cell growth regulation in response to collagen. The addition of C3 exoenzyme from Clostridium botulinum to specifically ribosylate and inhibit the function of the rho gene products inhibited cellular proliferation in a dose-dependent fashion. C3 exoenzyme exhibited broad cytostatic activity toward a number of tumor lines and induced G 0 /G 1 accumulation, cyclin A inhibition, and pronounced alterations in cell morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 49 publications
1
26
1
Order By: Relevance
“…There have also been many reports suggesting that occupation of the extracellular matrix receptor, integrin, is required for terminal muscle differentiation (21,45,70,74). A recent report has suggested that Rho family proteins work as mediators of integrin signaling (86). Taking these observations and our results together, it is tempting for us to speculate that integrin regulates muscle differentiation via the Rho family proteins.…”
Section: Discussioncontrasting
confidence: 47%
“…There have also been many reports suggesting that occupation of the extracellular matrix receptor, integrin, is required for terminal muscle differentiation (21,45,70,74). A recent report has suggested that Rho family proteins work as mediators of integrin signaling (86). Taking these observations and our results together, it is tempting for us to speculate that integrin regulates muscle differentiation via the Rho family proteins.…”
Section: Discussioncontrasting
confidence: 47%
“…9A). We treated cells with the C3 exoenzyme from Clostridium botulinum, which inhibits the function of RhoA, RhoB and RhoC; the other Rho family proteins Rac-1 and Cdc42 are poor C3 substrates (Udagawa and McIntyre, 1996). We also used Y-27632, a specific inhibitor of the Rho-associated coiled-coilforming protein serine/threonine kinase (ROCK) family of protein kinases (Narumiya et al, 2000).…”
Section: Cd8/mcsp Perturbs Intercellular Adhesion and The Actin Cytosmentioning
confidence: 99%
“…Keratinocytes expressing CD8 or CD8/MCSP were incubated with the following pharmacological inhibitors for 6 hours at 37°C: 5 µM Y-27632 (Calbiochem) (Narumiya et al, 2000); 5 µg ml -1 C3 exoenzyme from Clostridium botulinum (Calbiochem) (Udagawa and McIntyre, 1996); and 50 µM LY294002 (Sigma-Aldrich) (Pullen and Thomas, 1997).…”
Section: Function-blocking Experiments With Antibodies and Pharmacolomentioning
confidence: 99%
“…Therefore, we examined whether Rho is involved in MEF cell migration. Clostridium botulinum C3 exoenzyme is a specific inhibitor of Rho that works by irreversible ADP-ribosylation of Asn-41 in its effector region (19). We previously used this C3 toxin to block serum-induced Rho activation and actin stress fiber formation in MEF cells (11).…”
Section: Deficiency Of Csk Does Not Affect Rac Activation and Lamellimentioning
confidence: 99%